2012
DOI: 10.1371/journal.pone.0033046
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Transmission in a Community during a Seasonal Influenza A(H3N2) Outbreak (2010–2011) in Mongolia: A Community-Based Prospective Cohort Study

Abstract: BackgroundKnowledge of how influenza viruses spread in a community is important for planning and implementation of effective interventions, including social distancing measures. Households and schools are implicated as the major sites for influenza virus transmission. However, the overall picture of community transmission is not well defined during actual outbreaks. We conducted a community-based prospective cohort study to describe the transmission characteristics of influenza in Mongolia.Methods and Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
3
9
1
Order By: Relevance
“…Consistent with previous reports [8], [11][12], [21], we found household index cases were most likely to be young children (<9 years), and secondary infection risks were highest among young (<9 years) contacts. This suggests that interventions designed to interrupt household transmission may be particularly effective if they intervene on contacts with or between children (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous reports [8], [11][12], [21], we found household index cases were most likely to be young children (<9 years), and secondary infection risks were highest among young (<9 years) contacts. This suggests that interventions designed to interrupt household transmission may be particularly effective if they intervene on contacts with or between children (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Our estimated secondary infection risk (9.7%) falls in the mid-range of estimates reported from studies with similar designs (4%–17%) [10][12], [21][22]; however, we may have underestimated the actual value. Studies, such as ours, that test only symptomatic household members generally report lower estimates than those testing all household contacts of symptomatic cases [7]; however, our case definition was designed to facilitate collection of specimens from even mild illnesses.…”
Section: Discussioncontrasting
confidence: 45%
“…This age group effect appeared to decrease with age, such that larger numbers of older individuals (>65 years) conferred a protective effect for the household, although this relationship was only significant for H1N1pmd09. In general, this result is consistent with other studies that examined individual‐level influenza risk factors . A study in Tampa Bay, Florida, found that the seroprevalence of antibodies to H1N1pdm09 virus decreased by age, from the highest frequency of 53% in children aged 5‐17 years, to the lowest proportion of 11%‐13% in adults aged >50 years.…”
Section: Discussionsupporting
confidence: 89%
“…For each parameter set, we simulated the influenza trajectories under two demographic control policies, and then computed the difference in average secondary attack rates over 10 years (2015 to 2024) between two policies. doi:10.1371/journal.pone.0084961.g004 in other studies [61,82,83]. The above comparisons included some studies in which the SAR was measured empirically, though the relation between the simulated SAR and household size may be controlled by the model structure.…”
Section: Discussionmentioning
confidence: 99%